Mizoribine: A New Approach in the Treatment of Renal Disease. (8th November 2009) - Kawasaki, Yukihiko
Abstract : Mizoribine (MZB) is an imidazole nucleoside and an immunosuppressive agent. The immunosuppressive effect of MZB has been reported to be due to the inhibition of DNA synthesis in the S phase of the cell cycle. Because of its relative lack of toxicity, during the past decade MZB has been frequently used instead of azathioprine as a component of immunosuppressive drug regimens. MZB is being used to treat renal transplantation patients, IgA nephropathy, lupus erythematosus, and childhood nephrotic syndrome (NS), and some recent studies have assessed the efficacy of oral MZB pulse therapy for severe lupus nephritis, steroid-resistant NS, and frequently relapsing-steroid-dependent NS. This review summarizes the published findings on the efficacy of MZB for renal disease including IgA nephropathy, lupus nephritis, and NS, as well as of oral MZB pulse therapy for severe lupus nephritis and NS, and also the mechanism of the effect of oral MZB pulse therapy on the lymphocyte cell cycle.